2016
DOI: 10.7717/peerj.2627
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of group II introns in the chloroplast genome of the green algaOedocladium carolinianum(Chlorophyceae)

Abstract: BackgroundThe chloroplast genome sustained extensive changes in architecture during the evolution of the Chlorophyceae, a morphologically and ecologically diverse class of green algae belonging to the Chlorophyta; however, the forces driving these changes are poorly understood. The five orders recognized in the Chlorophyceae form two major clades: the CS clade consisting of the Chlamydomonadales and Sphaeropleales, and the OCC clade consisting of the Oedogoniales, Chaetophorales, and Chaetopeltidales. In the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 76 publications
2
17
1
Order By: Relevance
“…The presence of similar ncORFs in distant algal lineages, such as the Chlorophyceae (Brouard et al. ), Prasinophyceae (Lemieux et al. 2014b), and Trebouxiophyceae (this study, and Turmel et al.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The presence of similar ncORFs in distant algal lineages, such as the Chlorophyceae (Brouard et al. ), Prasinophyceae (Lemieux et al. 2014b), and Trebouxiophyceae (this study, and Turmel et al.…”
Section: Discussionmentioning
confidence: 54%
“…], Oedogonium cardiacum and Oedocladium carolinianun [Chlorophyceae; Brouard et al. , ], Parachlorella kessleri [Trebouxiophyceae; Turmel et al. 2009b], and Entransia fimbriata [Streptophyta, Turmel et al.…”
Section: Discussionmentioning
confidence: 99%
“…This would provide an accessible splicing apparatus and allow all but one intron to lose its own IEP ( Dai & Zimmerly, 2003 ; Lambowitz & Belfort, 2015 ; Lambowitz & Zimmerly, 2011 ). Brouard et al (2016) assumed that the freestanding orf1311 in Oedocladium (Chlorophyceae), with an intron encoded maturase, could function as promoter for splicing the ORF-less group II introns. Turmel, Otis & Lemieux (2016) detected introns in G. planctonica without ORFs, which may reflect an evolutionary pressure for a smaller and more compact intron structure enabling increased efficiency of splicing and mobility, when maturase activity is provided from elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…Also, outside of euglenoid chloroplast introns, very few species showed high pairwise similarity. For instance, Brouard et al (2016) found six group IIA introns in the chlorophyte Oedocladium carolinianum with high levels of nucleotide identities, which displayed over 80% pairwise identity. As well Turmel, Otis & Lemieux (2016) found several group II introns with high nucleotide identities also at various insertion sites, but only in small numbers.…”
Section: Resultsmentioning
confidence: 99%
“…Group II introns are actively involved in shaping their host genomes via mobility and horizontal transfer. Indeed, waves of group II intron proliferation were reported for some green algae [51, 52]. A remarkable example of intron propagation was found in cpDNA of the freshwater euglenid Euglena gracilis with almost all of its protein-coding genes interrupted [53].…”
Section: Organellar Group II Introns Are Abundantmentioning
confidence: 99%